The Falkland Basins: new structural model and hydrocarbon bearing prospects (by remote sensing and geoelectric data) - Korchagin, I. N.; Bakhmutov, V. G.; Levashov, S. P.; Solovyov, V. D.; Yakymchuk, N. A.; Bozhezha, D. N. (Ukrainian Antarctic Journal, 2014)
New results of geoelectric measurements were obtained during the season works of 17 Ukrainian Antarctic Expedition (XVII UAE, 2012). New data on the deep structure of the tectonic zone between the Falkland Islands and the South Shetland Islands make it possible to estimate the probable nature of geodynamic processes in this region. Deep geoelectric boundaries position and nature of their contacts near the South Shetland Islands and the Falkland Islands show a fundamentally different distribution of crustal and mantle layers in the Strait structures with continental and oceanic rock complexes. Some anomalous zones of “hydrocarbon deposit” type were detected in the South Falkland Basin shelf by the special technology of satellite data processing and interpretation using. The "deposit" type anomalies were mapped by FSPEF survey and anomalous polarized layers of "hydrocarbon deposit" type were studied by VERS sounding in the South Falkland Basin. These results are new and additional to oil and gas potential data for the South Falkland Basin shelf zone.